후과 골절이 동반된 경골 원위부 나선상 골절의 치료 - 김영성(Young Sung Kim); 이호민(Ho Min Lee); 김종필(Jong Pil Kim); 정필현(Phil Hyun Chung); 박순영(Soon Young Park) (The journal of the Korean Orthopaedic Association, 2021)
목적: 본 연구는 족관절 후과 골절을 동반한 경골 원위부 나선상 골절에서 경골에 대한 고정술로 골수강 내 금속정 고정술과 최소침습적 금속판 고정술의 기능적, 방사선학적 결과 및 후과 골절에 대한 고정술 유무에 따른 기능적, 방사선학적 결과를 비교하였다. 대상 및 방법: 2010년 1월부터 2018년 12월까지 본원에서 족관절 후과 골절을 동반한 경골 원위부 나선상 골절(AO Foundation/ Orthopaedic Trauma Association 분류 42-A1, B1, C1) 30명의 환자를 대상으로 연구하였다. 골수강 내 금속정 고정술을 시행한 16명을 intramedullary nailing (IMN)군으로, 최소 침습적 금속판 고정술을 시행한 14명을 minimally invasive plate osteosynthesis (MIPO)군으로 분류하여 양 군의 골유합 시기, 술 후 각 정렬, 족관절 후과 골편의 전위 정도 및 American Orthopaedic Foot and Ankle Society (AOFAS) 점수를 비교, 분석하였다. 또한 각 군에서 후과 골절에 대한 고정술 유무에 따른족관절 관절 운동 범위 및 AOFAS 점수를 비교하였다. 결과: 평균 골유합 시기는 IMN군에서 21.8주, MIPO군에서 23.1주였다(p=0.500). 최종 추시 평균 각 변형은 IMN군에서 관상면1.8°, 시상면 1.6°를 보였고, MIPO군에서 관상면 1.2°, 시상면 1.7°를 보였다(p=0.131, p=0.850). 술 후 및 최종 추시 방사선 사진상 양 군 모든 환자에서 족관절 후과 골편의 전위는 없었고, 최종 추시에서 족관절 관절염은 없었다. 임상적 평가로 최종 추시에서AOFAS 점수는 IMN군에서 평균 88.0점, MIPO 군에서 평균 87.6점을 보였다(p=0.905). 각 군에서 후과 골절에 대한 고정술 유무에 따른 족관절 관절 운동 범위 및 AOFAS 점수를 비교하였고 유의한 차이는 없었다. 결론: 족관절 후과 골절을 동반한 경골 원위부 나선상 골절의 치료에서 골수강 내 금속정 고정술과 최소 침습적 금속판 고정술은영상학적, 임상적 결과에서 차이가 없이 모두 우수한 결과를 보였다. Purpose: This study compared the functional and radiologic outcomes of intramedullary nailing (IMN) and minimally invasive plate osteosynthesis (MIPO) for tibia fractures in distal tibial spiral fractures combined with posterior malleolar fractures, as well as the functional and radiologic outcomes with and without fixation for posterior malleolar fractures. Materials and Methods: From January 2010 to December 2018 the radiological and clinical outcomes of 30 skeletally mature patients with tibial spiral fractures (AO Foundation/Orthopaedic Trauma Association classification 42-A1, B1, C1) combined with posterior malleolar fractures were analyzed. Sixteen patients were treated with IMN, and 14 patients were treated with MIPO. Depending on the surgical methods, the radiologic and clinical outcomes were compared by evaluating the bone union time, postoperative alignment, postoperative displacement of the posterior malleolar fragment, and American Orthopaedic Foot and Ankle Society (AOFAS) score. Moreover, the functional and clinical outcomes with and without fixation for posterior malleolar fractures were compared. Results: The mean bone union time was 21.8 weeks in the IMN group and 23.1 weeks in the MIPO group (p=0.500). At the final follow up, the mean alignment was coronal angulation of 1.8°, sagittal angulation of 1.6° in the IMN group and coronal angulation of 1.2° and sagittal angulation of 1.7° in the MIPO group (conoral angulation: p=0.131, sagittal angulation: p=0.850). The postoperative and final radiologic evaluation showed no displacement of the posterior malleolar fragment and excellent joint congruity in all cases. At the final follow-up, the mean AOFAS score was 88.0 on average in the IMN group and 87.6 on average in the MIPO group (p=0.905). The ankle range of motion and AOFAS score were similar in the fixation group and no fixation group for posterior malleolar fractures. Conclusion: Both IMN and MIPO for tibial spiral fractures combined with posterior malleolar fractures result in satisfactory radiological and clinical outcomes. KCI Citation Count: 1